Geographic variations and trends in percutaneous intervention for patients with and without acute myocardial infarction: A Japanese nationwide registry study - Yuichi Saito; Yuichiro Mori; Kyohei Yamaji; Shun Kohsaka; Hideki Wada; Hideki Ishii; Tetsuya Amano; Yoshio Kobayashi; Ken Kozuma (PLoS ONE, 2025)
Background A previous study demonstrated that the per capita volume of percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) was relatively uniform across the 47 prefectures in Japan, while elective PCIs for stable coronary artery disease showed wide regional variation. However, contemporary data remain limited. Methods The Japanese PCI (J-PCI) is a nationwide prospective registry covering most of the procedures performed within the country. PCI procedures in 2019 and 2023 were included and divided according to the indications: AMI versus non-AMI. The patterns of PCI procedures performed for AMI and non-AMI across all prefectures in Japan were evaluated. The associations of the non-AMI/AMI ratio with population, area, and the number of PCI-capable centers per prefecture were also assessed. Results A total of 494,746 PCI procedures were analyzed. The ratios between the highest and lowest prefectures were 4.0-fold in non-AMI and 1.9-fold in AMI in 2019 and 4.2-fold in non-AMI and 2.0-fold in AMI in 2023. The non-AMI/AMI ratio was positively correlated with the ratios of the number of PCI-capable centers to population and area per prefecture. Conclusions Geographic disparity was observed in the relative volume of PCI performed for AMI compared to non-AMI across Japan, potentially reflecting variations in the density of PCI-capable centers relative to the area and population of each prefecture.